Technologies of Critique - Thayer, Willy (Book collections on Project MUSE., 2020)
Technologies of Critique elaborates a critical practice that eludes critique's capture by institutional and market logics. Building on Chile's history of dissident art and its entangling of politics and aesthetics, Thayer engages continental philosophical traditions, to help pinpoint the technologies and media through which art intervenes critically in socio-political life.